A meta‐analysis: is low‐dose computed tomography a superior method for risky lung cancers screening population?. (26th November 2014) - Fu, Cuiping; Liu, Zilong; Zhu, Fen; Li, Shanqun; Jiang, Liyan
Abstract: Background and Aims: Low‐dose computed tomography (LDCT) has been proposed to be a new screening method to discover lung cancers in an early stage, especially those patients who are in a high risk of lung cancer. The primary objective of this meta‐analysis is to systematically review the effect of LDCT on screening for lung cancers among the risky population who are older than 49 years old and with smoking exposure. Methods: We searched randomized controlled clinical trials (RCTs) about comparing LDCT and chest X‐ray or usual caring from MEDLINE, EMBASE, and the Cochrane Library, Web of Knowledge and Springerlink databases (January 1994 to September 2013). Results: Nine RCTs met criteria for inclusion. Screening for lung cancer using LDCT resulted in a significantly higher number of stage I lung cancers [odds ratio (OR) 2.15, 95% confidence interval (CI) 1.88–2.47], higher number of total lung cancers (OR 1.31, 95% CI 1.20–1.43) than the control. Four of the nine studies indicated that the screening method did not decrease all‐cause mortality (OR 0.96, 95% CI 0.90–1.02), but decreased lung cancer‐specific mortality (OR 0.84, 95% CI 0.74–0.96). Five studies showed that LDCT had higher false‐positive rates (OR 8.7, 95% CI 7.43–10.19) than the group of control. Conclusion: Among the risky population, LDCT screening find out more stage I lung cancers and total lung cancers compared with chest X‐ray or no screening, and also shows advantages in decreasing lung cancer‐specific mortality, but the screening method does not decrease all‐cause mortality and have a higher false‐positive rates in diagnosis.